PENGEMBANGAN SISTEM INFORMASI GEOGRAFIS BERBASIS LOCAL GENIUS SUBAK UNTUK SISTEM DRAINASE WILAYAH MONANG-MANING, KECAMATAN DENPASAR BARAT, KOTAMADYA DENPASAR - Saputra Yasa, I Gede Adi (Jurnal Pendidikan Teknologi dan Kejuruan, 2014)
This study was aimed to (1) describe the problems in the drainage system in MonangManing area, (2) design the waterway of the drainage system based on subak local genius,and (3) implement the design model of drainage system based on subak local genius, especially for the route along Monang Maning area, in West Denpasar district – Denpasarmunicipality, by using the Geography Information System.This research used the software development method called System Development Life Cycle (SDLC), which was divided into 5 cycled phases; Planning, Analysis, Design,Implementation and Maintenance. This study produced some products based on the purposes of the study; (1) thedescription of the problems in the drainage system in Monang Maning which included thewaste disposal into the water, the land exploitation, the utilization of the buildings, the trespassing over the river border sign, sedimentation, the constriction of the river orwaterway, and the constriction or the loss of the water holes on the pavement due to theraising of the street height, (2) the waterway of the drainage system based on subak local genius, which involved the transformation of telabah gede / telabah aya into 9 (nine) primarydrainage waterways, the transformation of telabah pemaron gede into 16 (sixteen) secondarydrainage waterways and the transformation of telabah pemaron cenik into 27 tertiary drainage waterways, in which the division buildings for the drainage waterways based onsubak local genius in Monang Maning were 7 primary inlet-outlet control, 23 secondary inlet- outlet control and 28 tertiary inlet-outlet control, (3) the implementation of software usingMAPINFO, MySQL 5, VB 6 and ODBC 5.3 software. The software presented the primary,secondary and tertiary waterway design, the direction and the connectors on each waterway.